2014
DOI: 10.1590/s0004-28032014000200010
|View full text |Cite
|
Sign up to set email alerts
|

GASTRIC RESIDUAL VOLUME BY MAGNETIC RESSONANCE AFTER INTAKE OF MALTODEXTRIN AND GLUTAMINE: a randomized double-blind, crossover study

Abstract: ContextThe addition of glutamine in preoperative drinks may enhance the benefits of carbohydrate alone.ObjectivesTo evaluate the gastric residual volume after the intake of a beverage containing carbohydrate plus glutamine.MethodsEleven healthy volunteers (24-30 years-old) were randomized in a crossover fashion to intake 400 mL (4h before) and 200 mL (2h before) of a beverage containing either 12.5% maltodextrin (carbohydrate group) or 12.5% maltodextrin plus 15 g of glutamine (glutamine group) in two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
12
0
3
Order By: Relevance
“…Durante a análise de vários artigos foi possível observar que os pacientes permanecem mais tempo em jejum do que realmente é pedido, devido a fatores como: atraso nas cirurgias; transferências, falta de profissionais e equipamentos (Chaves, et al, 2019;Nascimento, et al, 2009;Oliveira, et al, 2009;Azevedo, et al, 2017;Lobo, et al, 2009;Brianez, et al, 2014). Callegaro, et al (2010) mostra, em seu trabalho, as experiências de alguns pacientes, como: atrasos, adiamentos ou cancelamentos.…”
Section: Resultsunclassified
“…Durante a análise de vários artigos foi possível observar que os pacientes permanecem mais tempo em jejum do que realmente é pedido, devido a fatores como: atraso nas cirurgias; transferências, falta de profissionais e equipamentos (Chaves, et al, 2019;Nascimento, et al, 2009;Oliveira, et al, 2009;Azevedo, et al, 2017;Lobo, et al, 2009;Brianez, et al, 2014). Callegaro, et al (2010) mostra, em seu trabalho, as experiências de alguns pacientes, como: atrasos, adiamentos ou cancelamentos.…”
Section: Resultsunclassified
“…Nenhum dos achados mostrou significância estatística, sendo possível deduzir que adicionar glutamina à já bem estabelecida CHO 12,5% é uma conduta segura com esvaziamento gástrico satisfatório em 2 a 3 horas. 17 Já Dock-Nascimento et al e Braga et al avaliaram o VRG através de aspiração de sonda nasogástrica introduzida durante anestesia. Em ambos estudos, a média do VRG entre os grupos foi similar, demonstrando que solução contendo glutamina não aumenta o resíduo gástrico.…”
Section: Discussionunclassified
“…The 20 studies identified by our search regarding clear liquids intake and gastric volumes did not report any event of aspiration or regurgitation. [ 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 ] The studies were of Low, or Very Low level of evidence. In eight studies, after overnight fasting, one group received water to consume medications and the other, received between 100 and 500 mL water till 2 hours before induction of anaesthesia.…”
Section: Adult Sectionmentioning
confidence: 99%
“…[ 75 ] Other studies which compared residual gastric volumes and pH after consumption of different kinds of liquids showed comparable gastric volumes and pH (LOE- Very Low to Low). [ 76 77 78 79 80 81 82 ] In a study assessing gastric volumes by gastroscopic aspiration after consumption of 200 mL water, the patients fasted for 40 to 75 min had gastric volumes similar to those fasted for 80-150 min (LOE- Moderate). [ 83 ] An earlier meta-analysis also concluded that there was no evidence that patients given liquid (including water, coffee, fruit juice, clear liquids and other drinks, e.g., isotonic drink, carbohydrate drink) 2-3 h prior to surgery had increased incidence of aspiration or regurgitation (LOE- High).…”
Section: Adult Sectionmentioning
confidence: 99%
See 1 more Smart Citation